VizieR Online Data Catalog: Long-term photometry and spectroscopy of EE Cep (Galan+, 2012) - Galan, C.; Mikolajewski, M.; Tomov, T.; Graczyk, D.; Apostolovska, G.; Barzova, I.; Bellas-Velidis, I.; Bilkina, B.; Blake, R. M.; Bolton, C. T.; Bondar, A.; Brat, L.; et al. (VizieR Online Data Catalog, 2012)
We present a catalog of photometric and spectroscopic data collected during and around of EE Cep eclipses in 1997, 2003 and 2008/9. The photometric data were obtained with 25 different instruments, mainly in Johnson-Cousins UBV(RI)C bands, and some small sets of the data were obtained with narrow interference filters, placed on, or around of H-alpha and H-beta lines. The photometry from the last two eclipses have been compiled into the set of consistent photometric data in UBV(RI)C bands, that has been used in the paper to modelling of the eclipses in EE Cep system. The 100 of spectra released in this catalog were obtained with 8 of different spectrographs at low, medium and high resolutions (R in range ~2000-48000). About half of them (54 spectra) cover narrow ranges of order 200 Angstroms with H-alpha, H-beta lines or NaI dublet, and the second part (46 spectra) cover longer ranges of wavelengths - several thousands of Angstroms in the visual domain or in the near infrared. (7 data files).
Keywords: binaries: eclipsing; Photometry: UBVRI